Book Markir Application Program for Student with Special Needs at Universitas Muhammadiyah Gresik - Rini Puji Astutik; Afakhrul Masub Bakhtiar; Zainal Mustakim; Muhammad Zamzamy (OJS Universitas Muhammadiyah Gresik, 2022)
Education is a right for all citizens regardless of differences in degrees, economic conditions or others, as well as for people in Gresik Regency. Books are an inseparable part of education. Therefore, every university must provide books as a means for the smooth learning process. One way to make it easier for students, especially those with special needs, to access library books is by using the Book Marking Application. This application is based on Augmented Reality so it requires a marker which will be scanned with an integrated camera with the Vuforia Augmented Reality Plugin. Students can choose books that are available on the library bookshelf without directly coming to the library, then the library will deliver the book according to the scanned marker information.